The Effect of Competence and Job Relevant Information on Budget Management Performance With Organizational Commitments as Intervening Variables in the Government of Klungkung Regency - Ni Made Juliastini (Global Researcher Network, 2022)
This study aims to determine and explain the effect of competence and job relevant information on organizational commitment and performance of budget managers and the role of organizational commitment in mediating the effect of competence and job relevant information on the performance of budget managers. The research population used is explanatory research. The research sample of 80 civil servants who were appointed as budget managers. Data collection techniques using observation, interviews and questionnaires. The analytical tool used in this study is PLS (Partial Least Square). The results of this study indicate that: (1) Competence has a positive and significant effect on organizational commitment. (2) Job Relevant Information has a positive and significant effect on organizational commitment. (3) Competence has a positive and significant effect on the performance of budget managers. (4) Job Relevant Information has a positive and significant effect on the performance of budget managers. (5) Organizational Commitment has a positive and significant effect on the performance of budget managers. (6) Organizational Commitment is a partial mediation of the effect of competence on the performance of budget managers. (7) Organizational Commitment is a partial mediation of the influence of Job Relevant Information on the performance of budget managers.